Business, human rights and transitional justice - Pietropaoli, Irene (Transitional justice, 2020)
Introduction -- Business and human rights and transitional justice -- Nuremberg and international criminal law -- Regional human rights systems -- Domestic criminal and civil liability -- Truth seeking processes -- Administrative reparation programmes -- Institutional reform -- Conclusion